2018
DOI: 10.3758/s13415-018-0575-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of self-construals on the ERP response to the rewards for self and mother

Abstract: Individual self-construal (independent vs. interdependent) could be temporarily modulated by the priming effect. Our previous studies have found that when Chinese participants gambled for mother and for self, outcome feedback evoked comparable neural responses between two conditions. However, it remains unclear if the response to rewards for mother and for self would differ after independence self-construal priming. In this study, we manipulated participants' self-construal (independent vs. interdependent) bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 64 publications
(96 reference statements)
1
11
0
Order By: Relevance
“…(A) All participants needed to finish the TG and simple gambling task twice each, and the sequence of the two players (likeable/dislikeable) in the gambling task was counterbalanced across participants. (B) The simple gambling task ( Zhang et al. , 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(A) All participants needed to finish the TG and simple gambling task twice each, and the sequence of the two players (likeable/dislikeable) in the gambling task was counterbalanced across participants. (B) The simple gambling task ( Zhang et al. , 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…, 1996 ; Fiske, 2010 ). Of specific interest to this study, the influence of social comparison on subjective feeling is modulated by interpersonal relationship ( Zhang et al. , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of ERP studies have begun to explore how the brain responds to outcomes related to others and found that ERP responses to others' feedback were similar to those elicited by the outcome of participants themselves (Fukushima & Hiraki, 2006Hu, Xu, & Mai, 2017;Liu, Hu, Shi, & Mai, 2018;Yu & Zhou, 2006;Zhu et al, 2018). Yu and Zhou (2006) reported that the FRN was elicited when individuals observed others' performance.…”
Section: Introductionmentioning
confidence: 99%
“…First, the difference wave approach can remove common underlying components that are insensitive to the win/loss manipulation (Bress, Smith, Foti, Klein, & Hajcak, 2012) and at the same time minimize potential overlaps between the FRN and other ERP components, particularly the P3 (Hajcak, Moser, Holroyd, & Simons, 2007;Holroyd & Krigolson, 2007). Second, we have successfully used the difference approach in relevant studies (e.g., Gu et al, 2016;Zhu, Gu, Wu, & Luo, 2015;Zhu et al, 2018). Thus, we created Bnegative-positive^and Bambiguous-positive^difference waves by subtracting the ERPs on positive outcome trials from the ERPs on negative and ambiguous outcome trials, respectively.…”
Section: Discussionmentioning
confidence: 99%